AMPK in skeletal muscle function and metabolism. Issue 4 (5th January 2018) - Kjøbsted, Rasmus; Hingst, Janne R.; Fentz, Joachim; Foretz, Marc; Sanz, Maria‐Nieves; Pehmøller, Christian; Shum, Michael; Marette, André; Mounier, Remi; Treebak, Jonas T.; Wojtaszewski, Jørgen F. P.; Viollet, Benoit; et al.
Abstract : Skeletal muscle possesses a remarkable ability to adapt to various physiologic conditions. AMPK is a sensor of intracellular energy status that maintains energy stores by fine‐tuning anabolic and catabolic pathways. AMPK's role as an energy sensor is particularly critical in tissues displaying highly changeable energy turnover. Due to the drastic changes in energy demand that occur between the resting and exercising state, skeletal muscle is one such tissue. Here, we review the complex regulation of AMPK in skeletal muscle and its consequences on metabolism ( e.g ., substrate uptake, oxidation, and storage as well as mitochondrial function of skeletal muscle fibers). We focus on the role of AMPK in skeletal muscle during exercise and in exercise recovery. We also address adaptations to exercise training, including skeletal muscle plasticity, highlighting novel concepts and future perspectives that need to be investigated. Furthermore, we discuss the possible role of AMPK as a therapeutic target as well as different AMPK activators and their potential for future drug development.— Kjøbsted, R., Hingst, J. R., Fentz, J., Foretz, M., Sanz, M.‐N., Pehmøller, C., Shum, M., Marette, A., Mounier, R., Treebak, J. T., Wojtaszewski, J. F. P., Viollet, B., Lantier, L. AMPK in skeletal muscle function and metabolism. FASEB J. 32, 1741–1777 (2018). www.fasebj.org